Fe-N-C cathode oxygen reduction catalyst for metal chloride salt assisted pyrolysis as well as preparation method and application of Fe-N-C cathode oxygen reduction catalyst
In the preparation process of Fe-N-C catalyst, metal chloride salt-assisted pyrolysis technology is used to increase the porosity and O2 transfer capacity of the catalyst, which solves the problems of low mass transfer efficiency and thickening of the layer in the prior art, and achieves higher oxygen reduction reaction activity and fuel cell power density.
Patent Information
- Application Number
- CN202411852350.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, the active sites of the Fe-N-C catalyst are embedded in the inner layer of the catalyst, resulting in low mass transfer efficiency in the oxygen reduction reaction, and low loading of the non-precious metal catalyst leads to thickening of the catalyst layer, increasing internal resistance, and hindering of O2 transmission.
By mixing ZIF-8 with the metal chloride salt in water, rotary evaporation and drying, the first pyrolysis is performed, so that the metal chloride salt molten state flows in the catalyst to increase the porosity; then mix with an added nitrogen source and iron salt, and then perform a second pyrolysis to obtain the Fe-N-C cathode oxygen reduction catalyst.
The pore structure and O2 transmission capacity of the catalyst are improved, the oxygen reduction reaction activity is enhanced, the thickness and internal resistance of the catalyst layer are reduced, and the peak power density of the fuel cell is improved.
Smart Images

Figure CN119725565A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalysts and preparation thereof, and specifically relates to a Fe-NC cathode oxygen reduction catalyst assisted by pyrolysis of metal chloride salts, and a preparation method and application thereof. Background Art
[0002] Proton exchange membrane fuel cell (PEMFC) is an efficient and environmentally friendly power generation system. In recent years, it has developed rapidly with the growing global demand for clean energy and sustainable energy conversion. PEMFC is widely used in automobiles, portable power supplies, and stationary power generation, and has broad market prospects.
[0003] However, due to the slow four-electron kinetics of the cathode oxygen reduction reaction, precious metal platinum (Pt) group catalysts are required. The scarcity and high cost of precious metals have always limited their large-scale application in fuel cells. In related technologies, metal single-atom nitrogen-doped carbon substrate (MNC) catalysts headed by Fe have reached the activity of commercial Pt / C. However, since most Fe-NC catalysts are obtained by pyrolysis, a large number of their active sites are embedded in the inner layer of the catalyst, which greatly affects mass transfer in the oxygen reduction reaction (ORR).
[0004] At present, the research on improving the mass transfer efficiency in the ORR process is still mainly focused on Pt-based catalysts. For example, the membrane electrode of Pt-based catalysts is optimized by improving the membrane resistance of O2. When the catalytic layer of Pt-based catalysts is thin enough, Knudsen diffusion accounts for a small proportion of the total resistance, and the O2 membrane resistance has the greatest impact in Pt-based catalysts. Therefore, high oxygen permeability ionomers are used in related technologies to reduce the O2 membrane resistance. However, for non-precious metal catalysts, there are obviously more issues to consider. Since the active center of the Fe-NC catalyst is a single atom, its load on the catalyst is very low. In order to achieve an increase in the power density of the fuel cell, more catalysts must be required, which also causes the catalyst layer to become thicker, followed by the problem of increased internal resistance of the battery and obstructed O2 transmission.
[0005] Therefore, there is an urgent need to develop non-precious metal catalysts to replace precious metals in order to reduce costs and improve the mass transfer performance of catalysts. Summary of the invention
[0006] In view of this, in order to solve at least one technical problem in the related art and other aspects, the present disclosure proposes a method for preparing a Fe-NC cathode oxygen reduction catalyst assisted by pyrolysis of a metal chloride salt, comprising:
[0007] The ZIF-8 and the metal chloride salt are mixed uniformly in water, and then dried by rotary evaporation to obtain a first composite solid;
[0008] In a protective atmosphere, the first composite solid is subjected to a first pyrolysis, so that the metal chloride salt flows in a molten state in the first composite solid, and a nitrogen-doped carbon substrate with increased porosity is obtained after acid washing, wherein the melting point of the metal chloride salt is lower than the pyrolysis temperature of the first pyrolysis;
[0009] grinding and mixing the nitrogen-doped carbon substrate with an external nitrogen source and an iron salt to obtain a second composite solid;
[0010] The second composite solid is subjected to a second pyrolysis in a protective atmosphere, and after acid washing and drying, a Fe-NC cathode oxygen reduction catalyst is obtained.
[0011] According to an embodiment of the present disclosure, the preparation method of ZIF-8 comprises:
[0012] The methanol solution of zinc nitrate hexahydrate and the methanol solution of 2-methylimidazole were mixed evenly, stirred at room temperature for 24 hours to obtain a suspension, and then centrifuged to obtain ZIF-8;
[0013] The molar ratio of zinc nitrate hexahydrate to 2-methylimidazole is 1:8.
[0014] According to an embodiment of the present disclosure, the molar ratio of ZIF-8 to the metal chloride salt is (1:10)-(1:50), and the metal chloride salt includes any one of potassium chloride, cesium chloride, sodium chloride, and lithium chloride.
[0015] According to an embodiment of the present disclosure, in the first pyrolysis, the pyrolysis temperature is 800° C., the pyrolysis time is 4 h, and the heating rate is 5° C. / min.
[0016] According to an embodiment of the present disclosure, the external nitrogen source includes 1,10-phenanthroline, the iron salt includes any one of ferric chloride, ferric acetylacetonate, and ferrocene, and the molar ratio of the nitrogen-doped carbon substrate, the external nitrogen source, and the iron salt is 30:2:1.
[0017] According to an embodiment of the present disclosure, in the second pyrolysis, the pyrolysis temperature is 800-1000° C., the pyrolysis time is 1 h, and the heating rate is 10° C. / min.
[0018] In another aspect of the present disclosure, a Fe-NC cathode oxygen reduction catalyst prepared by the above-mentioned preparation method is also provided, comprising a nitrogen-doped carbon substrate and an active center. The nitrogen-doped carbon substrate has a regular dodecahedral framework structure, and the porosity of the nitrogen-doped carbon substrate is 1500-2000 m 2 g -1 The active center is FeN4 loaded in the framework structure.
[0019] According to an embodiment of the present disclosure, the mass fraction of the active center is 1 wt%-3 wt%.
[0020] In another aspect of the present disclosure, an application of the aforementioned Fe-NC cathode oxygen reduction catalyst in a fuel cell is also proposed.
[0021] According to the embodiments of the present disclosure, the peak power density of the fuel cell is 1.3-1.6 W cm -2 .
[0022] According to the embodiments of the present disclosure, during the first pyrolysis process, the metal chloride salt exists in a molten state, flows in ZIF-8 and is etched to obtain a nitrogen-doped carbon substrate with a three-dimensional porous structure. This nitrogen-doped carbon substrate enriches the pore structure, which is beneficial to the dispersion of single atoms in the active center and the transmission of O2. At the same time, compared to hard templates such as SiO2 that require a harsh environment of hydrofluoric acid to remove, metal chloride salts only need a simple hydrochloric acid pickling to remove, which is environmentally friendly and simple in process. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 1 is a transmission electron microscope comparison diagram of Example 1 of the present disclosure before and after the second pyrolysis, wherein a is a transmission electron microscope diagram of the Fe-NC cathode oxygen reduction catalyst obtained after the second pyrolysis, and b is a transmission electron microscope diagram of the iron-nitrogen-carbon mixture before the second pyrolysis;
[0024] Figure 2 is a comparison diagram of pore size distribution before and after the second pyrolysis of Example 1 of the present disclosure, wherein a is a pore size distribution diagram of the Fe-NC cathode oxygen reduction catalyst obtained after the second pyrolysis, and b is a pore size distribution diagram of the iron-nitrogen-carbon mixture before the second pyrolysis;
[0025] Figure 3 It is the X-ray diffraction pattern of the Fe-NC cathode oxygen reduction catalyst prepared in Example 1 of the present disclosure.
[0026] Figure 4 is an X-ray fine absorption structure (XAFS) spectrum of the Fe-NC cathode oxygen reduction catalyst prepared in Example 1 of the present disclosure;
[0027] Figure 5 is a Fourier transform X-ray extended edge absorption structure (FT-EXAFS) of the Fe-NC cathode oxygen reduction catalyst prepared in Example 1 of the present disclosure;
[0028] Figure 6 is a linear sweep voltammetric graph of the Fe-NC cathode oxygen reduction catalyst prepared in Example 1 of the present disclosure in a 0.1 M perchloric acid solution;
[0029] Figure 7 is a polarization curve diagram of the catalyst in a proton exchange membrane hydrogen and oxygen fuel cell before and after the second pyrolysis of Example 1 of the present disclosure, wherein a is a polarization curve diagram of the Fe-NC cathode oxygen reduction catalyst obtained after the second pyrolysis in a proton exchange membrane hydrogen and oxygen fuel cell, and b is a polarization curve diagram of the iron-nitrogen-carbon mixture before the second pyrolysis in a proton exchange membrane hydrogen and oxygen fuel cell;
[0030] Figure 8 It is a polarization curve diagram of the catalyst in the proton exchange membrane hydrogen-air fuel cell before and after the second pyrolysis of Example 1 of the present disclosure, wherein a is the polarization curve diagram of the Fe-NC cathode oxygen reduction catalyst obtained after the second pyrolysis in the proton exchange membrane hydrogen-air fuel cell, and b is the polarization curve diagram of the iron-nitrogen-carbon mixture before the second pyrolysis in the proton exchange membrane hydrogen-air fuel cell. DETAILED DESCRIPTION
[0031] In order to make the objectives, technical solutions and advantages of the present disclosure more clearly understood, the present disclosure is further described in detail below in combination with specific embodiments and with reference to the accompanying drawings.
[0032] The endpoints and any values of the ranges disclosed in this disclosure are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this disclosure.
[0033] The terms used herein are only for describing specific embodiments and are not intended to limit the present disclosure. The terms "comprise", "include", etc. used herein indicate the existence of the features, steps, operations and / or components, but do not exclude the existence or addition of one or more other features, steps, operations or components.
[0034] All terms (including technical and scientific terms) used herein have the meanings commonly understood by those skilled in the art unless otherwise defined. It should be noted that the terms used herein should be interpreted as having a meaning consistent with the context of this specification and should not be interpreted in an idealized or overly rigid manner.
[0035] It should be noted that, unless otherwise defined, the technical terms or scientific terms used in the present disclosure shall have the usual meanings understood by persons with ordinary skills in the field to which the present disclosure belongs. If the full text involves descriptions such as "first", "second", etc., the descriptions such as "first", "second", etc. are only used to distinguish similar objects, and cannot be understood as indicating or implying their relative importance, order of precedence, or implicitly indicating the number of technical features indicated. It should be understood that the data described by "first", "second", etc. can be interchangeable under appropriate circumstances.
[0036] Similarly, in order to simplify the present disclosure and help understand one or more of the various disclosed aspects, in the above description of the exemplary embodiments of the present disclosure, the various features of the present disclosure are sometimes grouped together into a single embodiment, figure, or description thereof. The description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" and the like means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present disclosure. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0037] In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the fact that ordinary technicians in the field can implement it. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by this disclosure.
[0038] In the process of realizing the present disclosure, it was found that most of the research on ORR catalyst materials is committed to improving the intrinsic activity or site density of the site to significantly improve its half-wave potential under three-electrode conditions. However, in the actual operation of fuel cells, it is not only the problem of ORR reaction kinetics that needs to be considered, but also the problem of mass transfer limitation of catalysts at high current density should be paid attention to. Excluding the additional O2 transport resistance caused by liquid water, the intrinsic O2 mass transfer resistance of the fuel cell cathode is composed of the molecular diffusion resistance in the diffusion medium, the Knudsen diffusion resistance in the micropores of the catalyst layer, and the resistance of O2 dissolution and permeation of the ionomer membrane.
[0039] Therefore, the purpose of the present disclosure is to solve the problem of limited O2 mass transfer in non-precious metal single-atom catalysts at the cathode of proton exchange membrane fuel cells, and to provide a method for preparing an iron-nitrogen-carbon single-atom fuel cell cathode catalyst based on metal chloride salt-assisted pyrolysis. The present disclosure adds metal chloride salts, such as potassium chloride, to the ZIF-8 (Zeolitic Imidazolate Framework-8) precursor. During the pyrolysis process, the molten potassium chloride will etch the carbon carrier, thereby improving the material transfer capacity of the catalyst and achieving better ORR activity.
[0040] The present disclosure proposes a method for preparing a Fe-NC cathode oxygen reduction catalyst by metal chloride salt assisted pyrolysis, comprising the following steps S101 to S104:
[0041] Step S101: ZIF-8 and metal chloride salt are uniformly mixed in water, and then dried by rotary evaporation to obtain a first composite solid.
[0042] In some specific embodiments, step S101 includes mixing ZIF-8 and metal chloride salt in ultrapure water, stirring for 12 hours to mix evenly, rotary evaporating water, and drying in an oven to obtain a first composite solid. The rotary evaporation temperature can be selected to be 60°C and the rotation speed is 120 rpm; the drying method is forced air drying, the drying temperature is 120°C, and the time is 12 hours.
[0043] Step S102: In a protective atmosphere, the first composite solid is subjected to a first pyrolysis, so that the metal chloride salt flows in a molten state in the first composite solid, and a nitrogen-doped carbon substrate with increased porosity is obtained after acid washing, wherein the melting point of the metal chloride salt is lower than the pyrolysis temperature of the first pyrolysis.
[0044] In some specific embodiments, step S102 includes: placing the first composite solid in a quartz boat, calcining in a tube furnace at 800 ° C in an Ar atmosphere for 4 h; then acid-washing, filtering, drying and grinding the obtained black solid to obtain a black powder, thereby obtaining a nitrogen-doped carbon substrate. The acid-washing method can be hydrochloric acid acid washing, the hydrochloric acid concentration can be selected as 2 M, and the acid-washing time can be selected as 6 h; after acid washing, it can be selected to filter and separate, and the filter cake can be washed alternately with 4 L of water and ethanol.
[0045] Step S103: grinding and mixing the nitrogen-doped carbon substrate, the external nitrogen source and the iron salt to obtain a second composite solid;
[0046] In some specific embodiments, the grinding method can be manual grinding or automatic ball milling to introduce Fe into the NC substrate, and the time is preferably 15 minutes.
[0047] Step S104: in a protective atmosphere, the second composite solid is subjected to a second pyrolysis, and after acid washing and drying, a Fe-NC cathode oxygen reduction catalyst is obtained.
[0048] In some specific embodiments, the pickling method can be hydrochloric acid pickling, the hydrochloric acid concentration can be selected as 1 M, and the pickling time can be selected as 12 h; after pickling, suction filtration can be selected for separation, and the filter cake can be washed alternately with 4 L of water and ethanol.
[0049] According to the embodiments of the present disclosure, during the first pyrolysis process, the metal chloride salt exists in a molten state, flows in ZIF-8 and is etched to obtain a nitrogen-doped carbon substrate with a three-dimensional porous structure. This nitrogen-doped carbon substrate enriches the pore structure, which is beneficial to the dispersion of single atoms in the active center and the transmission of O2. At the same time, compared to hard templates such as SiO2 that require a harsh environment of hydrofluoric acid to remove, metal chloride salts only need a simple hydrochloric acid pickling to remove, which is environmentally friendly and simple in process.
[0050] According to an embodiment of the present disclosure, the preparation method of ZIF-8 comprises:
[0051] The methanol solution of zinc nitrate hexahydrate and the methanol solution of 2-methylimidazole were mixed evenly to obtain a suspension, and ZIF-8 was obtained after centrifugation;
[0052] Wherein, the mass ratio of zinc nitrate hexahydrate to 2-methylimidazole is 1:8.
[0053] According to the embodiments of the present disclosure, the methanol solution of zinc nitrate hexahydrate and the methanol solution of 2-methylimidazole ensure that the prepared ZIF-8 is a metal-organic framework material with a regular dodecahedral structure, which is conducive to the distribution of the active center FeN4 in the form of single atoms, thereby improving the catalytic mass transfer efficiency.
[0054] In some specific embodiments, the preparation method of ZIF-8 in step S101 includes: dispersing zinc nitrate hexahydrate (Zn(NO3)2·6H2O) and 2-methylimidazole (2-MeIm) in methanol at room temperature, stirring magnetically for 5 min, and recording them as solution A and solution B. After uniform dispersion, solution A is quickly poured into solution B and stirred at room temperature for 24 h to obtain a white suspension; the suspension is centrifuged, washed with methanol three times, and then dried in a vacuum oven at 60°C to obtain ZIF-8. The centrifugal separation speed is 10000 rpm and the time is 4 min.
[0055] According to an embodiment of the present disclosure, the molar ratio of ZIF-8 and the metal chloride salt is (1:10)-(1:50), for example, it can be 1:10, 1:15, 1:20, 1:25, 1:30, 1:35, 1:40, 1:45, 1:50, etc., and the metal chloride salt includes any one of potassium chloride, cesium chloride, sodium chloride, and lithium chloride.
[0056] According to an embodiment of the present disclosure, in the first pyrolysis, it is preferably calcined in a tubular furnace, with a pyrolysis temperature of 800° C., a pyrolysis time of 4 h, and a heating rate of 5° C. / min.
[0057] According to the embodiments of the present disclosure, the temperature of the first pyrolysis will affect the integrity and particle size of the ZIF-8 substrate. Under this condition, the particle size of the nitrogen-doped carbon substrate obtained is about 200 nm.
[0058] According to an embodiment of the present disclosure, the external nitrogen source includes 1,10-phenanthroline, the iron salt includes ferric chloride, and the molar ratio of the nitrogen-doped carbon substrate, the external nitrogen source and the iron salt is 30:2:1.
[0059] According to the embodiments of the present disclosure, single-atom iron is coordinated with nitrogen to form an active center. In order to make up for the deficiency of nitrogen source in the nitrogen-doped carbon substrate, an external nitrogen source can achieve better coordination with the iron atom to achieve better catalytic performance.
[0060] According to an embodiment of the present disclosure, in the second pyrolysis, it is preferably calcined in a tubular furnace, with a pyrolysis temperature of 800-1000° C., a pyrolysis time of 1 h, and a heating rate of 10° C. / min.
[0061] In another aspect of the present disclosure, a Fe-NC cathode oxygen reduction catalyst prepared by the above-mentioned preparation method is also provided, comprising a nitrogen-doped carbon substrate and an active center. The nitrogen-doped carbon substrate has a regular dodecahedral framework structure, and the porosity of the nitrogen-doped carbon substrate is 1500-2000 m 2 g -1 The active center is FeN4 loaded in the framework structure.
[0062] According to the embodiments of the present disclosure, the Fe-NC cathode oxygen reduction catalyst obtained by the aforementioned preparation method optimizes the pore structure of the catalyst, improves the O2 transmission capacity, and greatly improves the activity of the catalyst under ORR conditions.
[0063] According to an embodiment of the present disclosure, the mass fraction of the active center is 1 wt%-3 wt%, for example, it can be 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt%, 3 wt%, etc.
[0064] According to the embodiment of the present disclosure, the proportion of Fe is controlled when preparing the catalyst, and finally a single-atom Fe-NC catalyst with a mass fraction of 1 wt%-3 wt% is obtained. The experimental results verify that the Fe-NC catalyst prepared by this method has good activity.
[0065] In another aspect of the present disclosure, an application of the aforementioned Fe-NC cathode oxygen reduction catalyst in a fuel cell is also proposed.
[0066] According to the embodiments of the present disclosure, the pore structure characteristics of the Fe-NC cathode oxygen reduction catalyst are significantly improved through fine structural design and optimization. This improvement not only enhances the transmission efficiency of oxygen molecules (O2) inside the catalyst, but also effectively promotes the contact and reaction between oxygen molecules and the active center sites of the catalyst, thereby greatly improving the catalytic activity of the catalyst under oxygen reduction reaction (ORR) conditions.
[0067] According to the embodiments of the present disclosure, the peak power density of the fuel cell is 1.3-1.6 W cm -2 .
[0068] It should be noted that the described embodiments are only part of the embodiments of the present disclosure, rather than all of the embodiments. Based on the embodiments of the present disclosure, other embodiments obtained by ordinary technicians in the field without creative work are all within the scope of protection of the present disclosure.
[0069] Example 1
[0070] Zinc nitrate hexahydrate and 2-methylimidazole were dispersed in methanol at room temperature and magnetically stirred for 5 min, recorded as solution A and solution B. After uniform dispersion, solution A was quickly poured into solution B and stirred at room temperature for 24 h to obtain a white suspension. The suspension was centrifuged, washed with methanol three times, and then dried to obtain ZIF-8.
[0071] ZIF-8 and potassium chloride solid were dispersed in an appropriate amount of ultrapure water at a mass ratio of 1:2, stirred for 12 h, and the water was evaporated by rotary evaporation and dried in an oven to obtain a first composite solid.
[0072] The first composite solid was placed in a quartz boat and calcined in a tube furnace in an Ar atmosphere at 800° C. for 4 h. The obtained black solid was acid-washed, filtered, dried and ground to obtain a black powder on a nitrogen-doped carbon substrate.
[0073] The nitrogen-doped carbon substrate and 1,10-phenanthroline and FeCl2·4H2O were ground and mixed at a mass ratio of 200:25:14 for 15 min to obtain a second composite solid. The second composite solid was calcined at 800°C for 1 h in an Ar atmosphere, and then acid-washed, filtered, dried, and ground to obtain a single-atom Fe-NC proton exchange membrane fuel cell cathode oxygen reduction catalyst (referred to as Fe-NC cathode oxygen reduction catalyst or KCl-FeNC).
[0074] The Fe-NC cathode oxygen reduction catalyst prepared in Example 1 was characterized by X-ray absorption fine structure.
[0075] Figure 1 It is a transmission electron microscope comparison picture before and after the second pyrolysis of Example 1 of the present disclosure, wherein a is a transmission electron microscope picture of the Fe-NC cathode oxygen reduction catalyst obtained after the second pyrolysis, and b is a transmission electron microscope picture of the iron-nitrogen-carbon mixture before the second pyrolysis. Figure 2 It is a comparison diagram of the pore size distribution before and after the second pyrolysis of Example 1 of the present disclosure, wherein a is the pore size distribution diagram of the Fe-NC cathode oxygen reduction catalyst obtained after the second pyrolysis, and b is the pore size distribution diagram of the iron-nitrogen-carbon mixture before the second pyrolysis.
[0076] like Figure 1 , Figure 2 As shown, the Fe-NC catalyst assisted by high-temperature potassium chloride pyrolysis exhibits a rich pore structure and an increased specific surface area compared to the control sample, indicating that the metal chloride salt can etch the nitrogen-doped carbon substrate during high-temperature pyrolysis.
[0077] Figure 3 This is the X-ray diffraction pattern of the Fe-NC cathode oxygen reduction catalyst prepared in Example 1 of the present disclosure.
[0078] like Figure 3 As shown, no diffraction peak belonging to metallic Fe was found in the X-ray diffraction pattern of the Fe-NC cathode oxygen reduction catalyst, indicating that there are no large-sized Fe nanoparticles in the catalyst.
[0079] Figure 4 , Figure 5 It is the X-ray fine absorption structure (XAFS) spectrum and Fourier transform X-ray extended edge absorption structure (FT-EXAFS) spectrum of the Fe-NC cathode oxygen reduction catalyst prepared in Example 1 of the present disclosure.
[0080] like Figure 4 , Figure 5 As shown, no Fe-Fe scattering path was found in the space of the Fe-NC cathode oxygen reduction catalyst, further indicating that Fe is dispersed in the nitrogen-carbon carrier in the form of single atoms.
[0081] The potassium chloride-assisted pyrolysis single-atom iron-nitrogen-carbon-oxygen reduction cathode catalyst of Example 1 was subjected to a linear sweep voltammetry test in a 0.1 M perchloric acid solution.
[0082] Figure 6 It is a linear sweep voltammogram of the Fe-NC cathode oxygen reduction catalyst prepared in Example 1 of the present disclosure in 0.1 M perchloric acid solution.
[0083] like Figure 6 As shown in the figure, KCl-FeNC exhibited good acidic oxygen reduction activity in an acidic environment.
[0084] The potassium chloride-assisted pyrolysis single-atom iron-nitrogen-carbon-oxygen reduction cathode catalyst of Example 1 was polarized in a proton exchange membrane hydrogen-oxygen or hydrogen-air fuel cell.
[0085] Figure 7 , Figure 8 They are polarization curves of the Fe-NC cathode oxygen reduction catalyst prepared in Example 1 of the present disclosure in a proton exchange membrane hydrogen-oxygen or hydrogen-air fuel cell.
[0086] The polarization curve of the single-atom iron-nitrogen-carbon-oxygen reduction cathode catalyst of Example 1 assisted by potassium chloride pyrolysis was tested in a hydrogen-oxygen / air proton exchange membrane fuel cell. The results are as follows: Figure 7 , 8 As shown, KCl-FeNC exhibits excellent peak power density in hydrogen-oxygen / air fuel cells.
[0087] Example 2
[0088] Zinc nitrate hexahydrate and 2-methylimidazole were dispersed in methanol at room temperature and magnetically stirred for 5 min, recorded as solution A and solution B. After uniform dispersion, solution A was quickly poured into solution B and stirred at room temperature for 24 h to obtain a white suspension. The suspension was centrifuged, washed with methanol three times, and then dried to obtain ZIF-8.
[0089] ZIF-8 and potassium chloride solid were dispersed in an appropriate amount of ultrapure water at a mass ratio of 1:5, stirred for 12 h, and the water was evaporated by rotary evaporation and dried in an oven to obtain a first composite solid.
[0090] The first composite solid was placed in a quartz boat and calcined in a tube furnace in an Ar atmosphere at 800° C. for 4 h. The obtained black solid was acid-washed, filtered, dried and ground to obtain a black powder on a nitrogen-doped carbon substrate.
[0091] The nitrogen-doped carbon substrate and 1,10-phenanthroline and FeCl2·4H2O were ground and mixed at a mass ratio of 200:25:14 for 15 min to obtain a second composite solid. The second composite solid was calcined at 800°C for 1 h in an Ar atmosphere, and then acid-washed, filtered, dried, and ground to obtain a single-atom Fe-NC proton exchange membrane fuel cell cathode oxygen reduction catalyst (referred to as Fe-NC cathode oxygen reduction catalyst or KCl-FeNC).
[0092] The potassium chloride-assisted pyrolysis single-atom iron-nitrogen-carbon-oxygen reduction cathode catalyst of Example 2 was subjected to X-ray absorption fine structure, linear sweep voltammetry, and hydrogen-oxygen / air proton exchange membrane fuel cell polarization curve analysis, and the results were similar to those of Example 1.
[0093] Example 3
[0094] Zinc nitrate hexahydrate and 2-methylimidazole were dispersed in methanol at room temperature and magnetically stirred for 5 min, recorded as solution A and solution B. After uniform dispersion, solution A was quickly poured into solution B and stirred at room temperature for 24 h to obtain a white suspension. The suspension was centrifuged, washed with methanol three times, and then dried to obtain ZIF-8.
[0095] ZIF-8 and potassium chloride solid were dispersed in an appropriate amount of ultrapure water at a mass ratio of 1:10, stirred for 12 h, and the water was evaporated by rotary evaporation and dried in an oven to obtain a first composite solid.
[0096] The first composite solid was placed in a quartz boat and calcined in a tube furnace in an Ar atmosphere at 800° C. for 4 h. The obtained black solid was acid-washed, filtered, dried and ground to obtain a black powder on a nitrogen-doped carbon substrate.
[0097] The nitrogen-doped carbon substrate and 1,10-phenanthroline and FeCl2·4H2O were ground and mixed at a mass ratio of 200:25:14 for 15 min to obtain a second composite solid. The second composite solid was calcined at 800°C for 1 h in an Ar atmosphere, and then acid-washed, filtered, dried, and ground to obtain a single-atom Fe-NC proton exchange membrane fuel cell cathode oxygen reduction catalyst (referred to as Fe-NC cathode oxygen reduction catalyst or KCl-FeNC).
[0098] X-ray absorption fine structure, linear sweep voltammetry, and hydrogen-oxygen / air proton exchange membrane fuel cell polarization curve analysis were performed on the potassium chloride-assisted pyrolysis single-atom iron-nitrogen-carbon-oxygen reduction cathode catalyst of Example 3, and the results were similar to those of Example 1.
[0099] Example 4
[0100] Zinc nitrate hexahydrate and 2-methylimidazole were dispersed in methanol at room temperature and magnetically stirred for 5 min, recorded as solution A and solution B. After uniform dispersion, solution A was quickly poured into solution B and stirred at room temperature for 24 h to obtain a white suspension. The suspension was centrifuged, washed with methanol three times, and then dried to obtain ZIF-8.
[0101] ZIF-8 and potassium chloride solid were dispersed in an appropriate amount of ultrapure water at a mass ratio of 1:20, stirred for 12 h, and the water was evaporated by rotary evaporation and dried in an oven to obtain a first composite solid.
[0102] The first composite solid was placed in a quartz boat and calcined in a tube furnace in an Ar atmosphere at 800° C. for 4 h. The obtained black solid was acid-washed, filtered, dried and ground to obtain a black powder on a nitrogen-doped carbon substrate.
[0103] The nitrogen-doped carbon substrate and 1,10-phenanthroline and FeCl2·4H2O were ground and mixed at a mass ratio of 200:25:14 for 15 min to obtain a second composite solid. The second composite solid was calcined at 800°C for 1 h in an Ar atmosphere, and then acid-washed, filtered, dried, and ground to obtain a single-atom Fe-NC proton exchange membrane fuel cell cathode oxygen reduction catalyst (referred to as Fe-NC cathode oxygen reduction catalyst or KCl-FeNC).
[0104] X-ray absorption fine structure, linear sweep voltammetry, and hydrogen-oxygen / air proton exchange membrane fuel cell polarization curve analysis were performed on the potassium chloride-assisted pyrolysis single-atom iron-nitrogen-carbon-oxygen reduction cathode catalyst of Example 4, and the results were similar to those of Example 1.
[0105] Example 5
[0106] Zinc nitrate hexahydrate and 2-methylimidazole were dispersed in methanol at room temperature and magnetically stirred for 5 min, recorded as solution A and solution B. After uniform dispersion, solution A was quickly poured into solution B and stirred at room temperature for 24 h to obtain a white suspension. The suspension was centrifuged, washed with methanol three times, and then dried to obtain ZIF-8.
[0107] ZIF-8 and potassium chloride solid were dispersed in an appropriate amount of ultrapure water at a mass ratio of 1:2, stirred for 12 h, and the water was evaporated by rotary evaporation and dried in an oven to obtain a first composite solid.
[0108] The first composite solid was placed in a quartz boat and calcined in a tube furnace in an Ar atmosphere at 800° C. for 4 h. The obtained black solid was acid-washed, filtered, dried and ground to obtain a black powder on a nitrogen-doped carbon substrate.
[0109] The nitrogen-doped carbon substrate and 1,10-phenanthroline and FeCl2·4H2O were ground for 15 min and mixed evenly at a mass ratio of 200:25:14 to obtain a second composite solid. The second composite solid was calcined at 900°C for 1 h in an Ar atmosphere, and then acid-washed, filtered, dried, and ground to obtain a single-atom Fe-NC proton exchange membrane fuel cell cathode oxygen reduction catalyst (referred to as Fe-NC cathode oxygen reduction catalyst or KCl-FeNC).
[0110] The potassium chloride-assisted pyrolysis single-atom iron-nitrogen-carbon-oxygen reduction cathode catalyst of Example 5 was subjected to X-ray absorption fine structure, linear sweep voltammetry, and hydrogen-oxygen / air proton exchange membrane fuel cell polarization curve analysis, and the results were similar to those of Example 1.
[0111] Example 6
[0112] Zinc nitrate hexahydrate and 2-methylimidazole were dispersed in methanol at room temperature and magnetically stirred for 5 min, recorded as solution A and solution B. After uniform dispersion, solution A was quickly poured into solution B and stirred at room temperature for 24 h to obtain a white suspension. The suspension was centrifuged, washed with methanol three times, and then dried to obtain ZIF-8.
[0113] ZIF-8 and potassium chloride solid were dispersed in an appropriate amount of ultrapure water at a mass ratio of 1:5, stirred for 12 h, and the water was evaporated by rotary evaporation and dried in an oven to obtain a first composite solid.
[0114] The first composite solid was placed in a quartz boat and calcined in a tube furnace in an Ar atmosphere at 800° C. for 4 h. The obtained black solid was acid-washed, filtered, dried and ground to obtain a black powder on a nitrogen-doped carbon substrate.
[0115] The nitrogen-doped carbon substrate and 1,10-phenanthroline and FeCl2·4H2O were ground for 15 min and mixed evenly at a mass ratio of 200:25:14 to obtain a second composite solid. The second composite solid was calcined at 900°C for 1 h in an Ar atmosphere, and then acid-washed, filtered, dried, and ground to obtain a single-atom Fe-NC proton exchange membrane fuel cell cathode oxygen reduction catalyst (referred to as Fe-NC cathode oxygen reduction catalyst or KCl-FeNC).
[0116] The potassium chloride-assisted pyrolysis single-atom iron-nitrogen-carbon-oxygen reduction cathode catalyst of Example 6 was subjected to X-ray absorption fine structure, linear sweep voltammetry, and hydrogen-oxygen / air proton exchange membrane fuel cell polarization curve analysis, and the results were similar to those of Example 1.
[0117] Example 7
[0118] Zinc nitrate hexahydrate and 2-methylimidazole were dispersed in methanol at room temperature and magnetically stirred for 5 min, recorded as solution A and solution B. After uniform dispersion, solution A was quickly poured into solution B and stirred at room temperature for 24 h to obtain a white suspension. The suspension was centrifuged, washed with methanol three times, and then dried to obtain ZIF-8.
[0119] ZIF-8 and potassium chloride solid were dispersed in an appropriate amount of ultrapure water at a mass ratio of 1:10, stirred for 12 h, and the water was evaporated by rotary evaporation and dried in an oven to obtain a first composite solid.
[0120] The first composite solid was placed in a quartz boat and calcined in a tube furnace in an Ar atmosphere at 800° C. for 4 h. The obtained black solid was acid-washed, filtered, dried and ground to obtain a black powder on a nitrogen-doped carbon substrate.
[0121] The nitrogen-doped carbon substrate and 1,10-phenanthroline and FeCl2·4H2O were ground for 15 min and mixed evenly at a mass ratio of 200:25:14 to obtain a second composite solid. The second composite solid was calcined at 900°C for 1 h in an Ar atmosphere, and then acid-washed, filtered, dried, and ground to obtain a single-atom Fe-NC proton exchange membrane fuel cell cathode oxygen reduction catalyst (referred to as Fe-NC cathode oxygen reduction catalyst or KCl-FeNC).
[0122] The potassium chloride-assisted pyrolysis single-atom iron-nitrogen-carbon-oxygen reduction cathode catalyst of Example 7 was subjected to X-ray absorption fine structure, linear sweep voltammetry, and hydrogen-oxygen / air proton exchange membrane fuel cell polarization curve analysis, and the results were similar to those of Example 1.
[0123] Example 8
[0124] Zinc nitrate hexahydrate and 2-methylimidazole were dispersed in methanol at room temperature and magnetically stirred for 5 min, recorded as solution A and solution B. After uniform dispersion, solution A was quickly poured into solution B and stirred at room temperature for 24 h to obtain a white suspension. The suspension was centrifuged, washed with methanol three times, and then dried to obtain ZIF-8.
[0125] ZIF-8 and potassium chloride solid were dispersed in an appropriate amount of ultrapure water at a mass ratio of 1:20, stirred for 12 h, and the water was evaporated by rotary evaporation and dried in an oven to obtain a first composite solid.
[0126] The first composite solid was placed in a quartz boat and calcined in a tube furnace in an Ar atmosphere at 800° C. for 4 h. The obtained black solid was acid-washed, filtered, dried and ground to obtain a black powder on a nitrogen-doped carbon substrate.
[0127] The nitrogen-doped carbon substrate and 1,10-phenanthroline and FeCl2·4H2O were ground for 15 min and mixed evenly at a mass ratio of 200:25:14 to obtain a second composite solid. The second composite solid was calcined at 900°C for 1 h in an Ar atmosphere, and then acid-washed, filtered, dried, and ground to obtain a single-atom Fe-NC proton exchange membrane fuel cell cathode oxygen reduction catalyst (referred to as Fe-NC cathode oxygen reduction catalyst or KCl-FeNC).
[0128] The potassium chloride-assisted pyrolysis single-atom iron-nitrogen-carbon-oxygen reduction cathode catalyst of Example 8 was subjected to X-ray absorption fine structure, linear sweep voltammetry, and hydrogen-oxygen / air proton exchange membrane fuel cell polarization curve analysis, and the results were similar to those of Example 1.
[0129] Example 9
[0130] Zinc nitrate hexahydrate and 2-methylimidazole were dispersed in methanol at room temperature and magnetically stirred for 5 min, recorded as solution A and solution B. After uniform dispersion, solution A was quickly poured into solution B and stirred at room temperature for 24 h to obtain a white suspension. The suspension was centrifuged, washed with methanol three times, and then dried to obtain ZIF-8.
[0131] ZIF-8 and potassium chloride solid were dispersed in an appropriate amount of ultrapure water at a mass ratio of 1:2, stirred for 12 h, and the water was evaporated by rotary evaporation and dried in an oven to obtain a first composite solid.
[0132] The first composite solid was placed in a quartz boat and calcined in a tube furnace in an Ar atmosphere at 800° C. for 4 h. The obtained black solid was acid-washed, filtered, dried and ground to obtain a black powder on a nitrogen-doped carbon substrate.
[0133] The nitrogen-doped carbon substrate and 1,10-phenanthroline and FeCl2·4H2O were ground for 15 min and mixed evenly at a mass ratio of 200:25:14 to obtain a second composite solid. The second composite solid was calcined at 1000°C for 1 h in an Ar atmosphere, and then acid-washed, filtered, dried, and ground to obtain a single-atom Fe-NC proton exchange membrane fuel cell cathode oxygen reduction catalyst (referred to as Fe-NC cathode oxygen reduction catalyst or KCl-FeNC).
[0134] The potassium chloride-assisted pyrolysis single-atom iron-nitrogen-carbon-oxygen reduction cathode catalyst of Example 9 was subjected to X-ray absorption fine structure, linear sweep voltammetry, and hydrogen-oxygen / air proton exchange membrane fuel cell polarization curve analysis, and the results were similar to those of Example 1.
[0135] Example 10
[0136] Zinc nitrate hexahydrate and 2-methylimidazole were dispersed in methanol at room temperature and magnetically stirred for 5 min, recorded as solution A and solution B. After uniform dispersion, solution A was quickly poured into solution B and stirred at room temperature for 24 h to obtain a white suspension. The suspension was centrifuged, washed with methanol three times, and then dried to obtain ZIF-8.
[0137] ZIF-8 and potassium chloride solid were dispersed in an appropriate amount of ultrapure water at a mass ratio of 1:5, stirred for 12 h, and the water was evaporated by rotary evaporation and dried in an oven to obtain a first composite solid.
[0138] The first composite solid was placed in a quartz boat and calcined in a tube furnace in an Ar atmosphere at 800° C. for 4 h. The obtained black solid was acid-washed, filtered, dried and ground to obtain a black powder on a nitrogen-doped carbon substrate.
[0139] The nitrogen-doped carbon substrate and 1,10-phenanthroline and FeCl2·4H2O were ground for 15 min and mixed evenly at a mass ratio of 200:25:14 to obtain a second composite solid. The second composite solid was calcined at 1000°C for 1 h in an Ar atmosphere, and then acid-washed, filtered, dried, and ground to obtain a single-atom Fe-NC proton exchange membrane fuel cell cathode oxygen reduction catalyst (referred to as Fe-NC cathode oxygen reduction catalyst or KCl-FeNC).
[0140] The potassium chloride-assisted pyrolysis single-atom iron-nitrogen-carbon-oxygen reduction cathode catalyst of Example 10 was subjected to X-ray absorption fine structure, linear sweep voltammetry, and hydrogen-oxygen / air proton exchange membrane fuel cell polarization curve analysis, and the results were similar to those of Example 1.
[0141] Embodiment 11
[0142] Zinc nitrate hexahydrate and 2-methylimidazole were dispersed in methanol at room temperature and magnetically stirred for 5 min, recorded as solution A and solution B. After uniform dispersion, solution A was quickly poured into solution B and stirred at room temperature for 24 h to obtain a white suspension. The suspension was centrifuged, washed with methanol three times, and then dried to obtain ZIF-8.
[0143] ZIF-8 and potassium chloride solid were dispersed in an appropriate amount of ultrapure water at a mass ratio of 1:10, stirred for 12 h, and the water was evaporated by rotary evaporation and dried in an oven to obtain a first composite solid.
[0144] The first composite solid was placed in a quartz boat and calcined in a tube furnace in an Ar atmosphere at 800° C. for 4 h. The obtained black solid was acid-washed, filtered, dried and ground to obtain a black powder on a nitrogen-doped carbon substrate.
[0145] The nitrogen-doped carbon substrate and 1,10-phenanthroline and FeCl2·4H2O were ground for 15 min and mixed evenly at a mass ratio of 200:25:14 to obtain a second composite solid. The second composite solid was calcined at 1000°C for 1 h in an Ar atmosphere, and then acid-washed, filtered, dried, and ground to obtain a single-atom Fe-NC proton exchange membrane fuel cell cathode oxygen reduction catalyst (referred to as Fe-NC cathode oxygen reduction catalyst or KCl-FeNC).
[0146] The potassium chloride-assisted pyrolysis single-atom iron-nitrogen-carbon-oxygen reduction cathode catalyst of Example 11 was subjected to X-ray absorption fine structure, linear sweep voltammetry, and hydrogen-oxygen / air proton exchange membrane fuel cell polarization curve analysis, and the results were similar to those of Example 1.
[0147] Example 12
[0148] Zinc nitrate hexahydrate and 2-methylimidazole were dispersed in methanol at room temperature and magnetically stirred for 5 min, recorded as solution A and solution B. After uniform dispersion, solution A was quickly poured into solution B and stirred at room temperature for 24 h to obtain a white suspension. The suspension was centrifuged, washed with methanol three times, and then dried to obtain ZIF-8.
[0149] ZIF-8 and potassium chloride solid were dispersed in an appropriate amount of ultrapure water at a mass ratio of 1:20, stirred for 12 h, and the water was evaporated by rotary evaporation and dried in an oven to obtain a first composite solid.
[0150] The first composite solid was placed in a quartz boat and calcined in a tube furnace in an Ar atmosphere at 800° C. for 4 h. The obtained black solid was acid-washed, filtered, dried and ground to obtain a black powder on a nitrogen-doped carbon substrate.
[0151] The nitrogen-doped carbon substrate and 1,10-phenanthroline and FeCl2·4H2O were ground for 15 min and mixed evenly at a mass ratio of 200:25:14 to obtain a second composite solid. The second composite solid was calcined at 1000°C for 1 h in an Ar atmosphere, and then acid-washed, filtered, dried, and ground to obtain a single-atom Fe-NC proton exchange membrane fuel cell cathode oxygen reduction catalyst (referred to as Fe-NC cathode oxygen reduction catalyst or KCl-FeNC).
[0152] The potassium chloride-assisted pyrolysis single-atom iron-nitrogen-carbon-oxygen reduction cathode catalyst of Example 12 was subjected to X-ray absorption fine structure, linear sweep voltammetry, and hydrogen-oxygen / air proton exchange membrane fuel cell polarization curve analysis, and the results were similar to those of Example 1.
[0153] The relevant test results of Examples 1-12 are summarized in Table 1 below.
[0154] Table 1:
[0155]
[0156] As can be seen from Table 1, with the increase of the molar ratio of ZIF-8 and metal chloride salt, the specific surface area of the final catalyst first increases and then decreases, and the catalytic activity also first increases and then decreases. The reason is because of the etching effect of metal chloride salts on the nitrogen-doped carbon substrate. The right amount of etching can help to expose the active sites and the mass transfer process, but excessive etching will cause the collapse of its skeleton. Among them, the most preferred molar ratio of ZIF-8 and metal chloride salt is 1:30. At the same time, with the increase of the second pyrolysis temperature, the activity of the final catalyst first increases and then decreases, and 900°C is preferred. Although the specific surface area is higher at 800°C, the internal resistance is too large due to the insufficient conductivity of the catalyst. At 1000°C, the density of single-atom active sites decreases due to the decrease in the nitrogen content of the substrate.
[0157] The specific embodiments described above further illustrate the purpose, technical solutions and beneficial effects of the present disclosure. It should be understood that the above description is only a specific embodiment of the present disclosure and is not intended to limit the present disclosure. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present disclosure should be included in the protection scope of the present disclosure.
Claims
1. A method for preparing a Fe-NC cathode oxygen reduction catalyst assisted by pyrolysis of a metal chloride salt, comprising: The ZIF-8 and the metal chloride salt are mixed uniformly in water, and then dried by rotary evaporation to obtain a first composite solid; In a protective atmosphere, the first composite solid is subjected to a first pyrolysis, so that the metal chloride salt flows in the first composite solid in a molten state, and a nitrogen-doped carbon substrate with increased porosity is obtained after acid washing, wherein the melting point of the metal chloride salt is lower than the pyrolysis temperature of the first pyrolysis; Grinding and mixing the nitrogen-doped carbon substrate with an external nitrogen source and an iron salt to obtain a second composite solid; The second composite solid is pyrolyzed for the second time in a protective atmosphere, and then acid-washed and dried to obtain a Fe-NC cathode oxygen reduction catalyst.
2. The preparation method according to claim 1, wherein The preparation method of ZIF-8 comprises: The methanol solution of zinc nitrate hexahydrate and the methanol solution of 2-methylimidazole were mixed evenly, stirred at room temperature for 24 hours to obtain a suspension, and then centrifuged to obtain ZIF-8; Wherein, the molar ratio of zinc nitrate hexahydrate to 2-methylimidazole is 1:
8.
3. The preparation method according to claim 1, wherein The molar ratio of ZIF-8 to the metal chloride salt is (1:10)-(1:50), and the metal chloride salt includes any one of potassium chloride, cesium chloride, sodium chloride, and lithium chloride.
4. The preparation method according to claim 1, wherein In the first pyrolysis, the pyrolysis temperature is 800°C, the pyrolysis time is 4h, and the heating rate is 5°C / min.
5. The preparation method according to claim 1, wherein The external nitrogen source includes 1,10-phenanthroline, the iron salt includes any one of ferric chloride, ferric acetylacetonate, and ferrocene, and the molar ratio of the nitrogen-doped carbon substrate, the external nitrogen source, and the iron salt is 30:2:
1.
6. The preparation method according to claim 1, wherein In the second pyrolysis, the pyrolysis temperature is 800-1000°C, the pyrolysis time is 1 hour, and the heating rate is 10°C / min.
7. A Fe-NC cathode oxygen reduction catalyst obtained by the preparation method according to any one of claims 1 to 6, comprising: A nitrogen-doped carbon substrate having a regular dodecahedral framework structure, wherein the porosity of the nitrogen-doped carbon substrate is 1500-2000 m 2 g -1 ; Active center, the active center is FeN4 loaded in the framework structure.
8. The Fe-NC cathode oxygen reduction catalyst according to claim 7, wherein: The mass fraction of the active center is 1 wt%-3 wt%.
9. Use of the Fe-NC cathode oxygen reduction catalyst according to any one of claims 7 or 8 in a fuel cell.
10. The use according to claim 9, wherein: The peak power density of the fuel cell is 1.3-1.6 W cm -2 .
Citation Information
Patent Citations
Porous carbon material supported metal oxygen reduction catalyst as well as preparation method and application thereof
CN116169305A
Precious metal nanoparticle synergistic transition metal monatomic catalyst, preparation and application
CN117497787A
FePc-coated NiFe-WNC composite material and rechargeable zinc air battery
CN118472288A
Ordered graded porous Fe-N-C oxygen reduction catalyst as well as preparation method and application thereof
CN118572129A
Non-Noble Metal Electrocatalysts for Oxygen Depolarized Cathodes and Their Uses
US20150340705A1
Cited By
NbN nanoparticle composite FeNC catalyst as well as preparation method and application thereof
CN120989662A